Nonabelian Case of Hopf Galois Structures on Nonnormal Extensions of Degree pqw (European Journal of Pure and Applied Mathematics, 2023)
We look at Hopf Galois structures with square free pqw degree on separable field extensions (nonnormal) L/K. Where E/K is the normal closure of L/K, the group permutation of degree pqw is G = Gal(E/K). We study details of the nonabelian case, where Jl = ⟨σ, [τ, αl ]⟩ is a nonabelian regular subgroup of Hol(N) for 1 ≤ l ≤ w − 1. We first find the group permutation G, and then the Hopf Galois structures for each G. In this case, there exists four G such that the Hopf Galois structures are admissible within the field extensions L/K.
Keywords: Hopf Galois structures; field extensions; groups of square free order; Sophie Germain primes